Kombinasi Inulin Umbi Dahlia-Lactobacillus sp yang Mengoptimalkan Perkembangan Mikroflora Usus dan Pertumbuhan Persilangan Ayam Pelung-Leghorn (COMBINATION INULIN OF DAHLIA VARIABILIS TUBERS-LACTOBACILLUS SP OPTIMIZING THE DEVELOPMENT OF INTESTINAL MICRO - Faradila, Soraya; Suthama, Nyoman; Sukamto, Bambang (Jurnal Veteriner; Vol 17 No 2 (2016), 2016)
The research was aimed to evaluate the combination effect of inulin dahlia tuber and Lactobacillus spdevelopment micro flora on intestinal and productivity of crossbred local chicken. The present researchwas assigned in a completely randomized design with factorial pattern, 2x3. The first factor was two levelsof dahlia tuber powder as inulin source 0.8% (A1) and 1.2% (A2), and, the second factor was three levels ofLactobacillus sp namely, without Lactobacillus sp (B0), 1.2 mL (108 cfu/mL) (B1) and 2.4 mL (108 cfu/mL)(B2). Each treatment combination was replicated four times with seven birds each. Parameters observedwere total of lactic acid bacteria (BAL), Escherichia coli, pH and body weight gain. The results showed thatfeeding inulin dahlia tubers at 1.2% and Lactobacillus sp at 1.2 mL (108 cfu/mL) sp either in partial orinteraction significantly (P<0.05) affected the total LAB, E. coli, pH and body weight gain. In conclusion,combination of inulin from dahlia tubers and Lactobacillus can increase total LAB and body weight gain,decrease total E. coli and pH.
Keywords: inulin, Lactobacillus sp, micro flora, crossbred local chicken